Go!

1

2

3

4

5

6

7

8

9

0

x

y

(◻)

◻/◻

◻^{2}

◻^{◻}

√◻

∞

e

π

ln

log

lim

d/dx

d^{□}/dx^{□}

∫

∫^{◻}

>

<

>=

<=

sin

cos

tan

cot

sec

csc

asin

acos

atan

acot

asec

acsc

sinh

cosh

tanh

coth

sech

csch

asinh

acosh

atanh

acoth

asech

acsch

1

Example

$y'''-y''-y'+y=2e^{-x}+3$

2

Moving the term $y'\left(-1\right)$ to the other side of the equation with opposite sign

$y+y''\left(-1\right)+y'''=y'+3+2e^{-x}$

3

Moving the term $y''\left(-1\right)$ to the other side of the equation with opposite sign

$y+y'''=y''+y'+3+2e^{-x}$

Access detailed step by step solutions to millions of problems, growing every day!